PENGEMBANGAN E-BOOK BERBASIS APLIKASI FLIP PDF CORPORATE EDITION MATERI CERITA FIKSI DAN NON FIKSI SISWA KELAS V SEKOLAH DASAR - Ivan Maulana Saputra; Denna Delawanti C; Dwi Agus Setiawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
In Indonesian language learning in elementary schools, there is a tendency to use limited teaching materials, especially those focused on textbooks. This can cause students to feel less interested and potentially reduce their enthusiasm in following the learning materials. The purpose of this study was to determine the validity, practicality, and effectiveness of the development of Flip PDF Corporate Edition-based E-Books for fictional and non-fiction story materials for fifth-grade elementary school students. This development research uses the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data analysis in this study uses qualitative and quantitative methods. Based on the results of the assessment of media experts, the percentage was 91.66%, material experts 93.18%, language experts 100%, from the three experts, an average of 94.95% was obtained with the category "very valid". The results of the teacher's practicality test obtained 93.75% with the category "very practical", while limited trials by students obtained 88.88% with the category "very practical", and extensive trials obtained 90.65% with the category "very practical". Meanwhile, the effectiveness test using the N-Gain score obtained 0.8 with the "moderate" category and in percentage terms obtained 82.1 with the "Very Effective" category. So it can be concluded that the use of the Flip PDF Corporate Edition-based E-Book is valid, practical, and effective for use as Indonesian language teaching materials in Elementary Schools.